2017
DOI: 10.26477/idj.v39i1.118
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Endodontic Fear in Different Age Groups for Iraqi Endodontic Patients

Abstract: Background: Fear, anxiety and phobia are major complications for both patient and dental care providers despite the technological advances that have made dentistry less painful and less uncomfortable. This study aimed to identify the most common pathways of fear related to root canal treatment in different aged groups for both genders. Materials and methods:The study sample consisted of (800) patients were selected, aged (20-59) years old from patients attending the Al-Shiekh Omar specialized dental center. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This may be due to the differences in the hygiene practices or socioeconomic status of the two groups. [38][39][40][41][42] In this present study, periodontal parameters; such as PLI, BOP, PPD, and CAL; were higher in the AS-P group than in the other three groups. Al-Taweel et al, 19 Yagnik et al, 20 Al-Ghurabi et al, 43 and Shaker and Hashem 44 reported similar findings and concluded that the inflammatory response due to plaque biofilms, which produce an extensive variety of bacterial by-products; such as toxins, enzymes, and hydrogen sulphide (H 2 S); illicit accelerate periodontal tissue deterioration; such as periodontal ligaments loss, pocket formation, bone resorption, and tooth loss.…”
mentioning
confidence: 76%
“…This may be due to the differences in the hygiene practices or socioeconomic status of the two groups. [38][39][40][41][42] In this present study, periodontal parameters; such as PLI, BOP, PPD, and CAL; were higher in the AS-P group than in the other three groups. Al-Taweel et al, 19 Yagnik et al, 20 Al-Ghurabi et al, 43 and Shaker and Hashem 44 reported similar findings and concluded that the inflammatory response due to plaque biofilms, which produce an extensive variety of bacterial by-products; such as toxins, enzymes, and hydrogen sulphide (H 2 S); illicit accelerate periodontal tissue deterioration; such as periodontal ligaments loss, pocket formation, bone resorption, and tooth loss.…”
mentioning
confidence: 76%
“…1,2 Periodontitis encompasses the existence of inflammation in the periodontal tissues, the development of periodontal pockets, a breakdown of connective tissue, alveolar bone loss, and potential tooth loss. [3][4][5][6][7] Despite their beneficial role in eradicating pathogens, inflammation is a double-edged sword; it is considered a crucial source of periodontal tissue destruction, involving leukocytes, complement, and reactive oxygen species (ROS). 8 ROS seem to be short-lived, extremely reactive oxygen-reduced radicals, including superoxide , hydrogen peroxide (H 2 O 2 ), the hydroxyl radical (OH), and singlet oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…However, a drill can effectively remove harmful patient experiences ( Arora et al, 2012 ). Consequently, it is crucial to address anxious and uncooperative youngsters using a painless, noninvasive method ( Kotb et al, 2009 ; Saeed, Hussein & Mahmood, 2017 ; Hussein, Saeed & Al-Zaka, 2017 ).…”
Section: Introductionmentioning
confidence: 99%